CORPORATE SOCIAL RESPONSOBILITY RESEARCH METHODS ANALYSIS - Sapkauskiene, Alfreda; Leitoniene, Sviesa (European Scientific Journal, ESJ, 2014)
Although the last decade of the corporate social responsibility (CSR) is talking more and more, but it is accompanied by many uncertainties that affect the same social responsibility activities and the disclosure of social information to stakeholders. The problem remains that the different studies of CSR provide mixed results about nature and scope of social information, about theories on corporate social information disclosure behaviour and about CSR impact to company’s reputation and financial performance. Therefore the aim of this article is to systematize research of CRS information disclosure. In order to narrow the scope of the study, the object of the study involves scientific studies which were carried out during the period of 2008-2013 and which deal with social information disclosure in the banking sector. The main reason why the banking sector was selected is that although banks actively participate in activities of socially responsibility companies, banks and other financial institutions are often excluded from scientific studies due to their nature of activities. The carried out analysis of CSR research methods showed that most often method used in CRS research is the content analysis method, and only less than a half of the analyzed scientific studies use other research methods in addition to the content analysis, such as correlation and regression analysis. The researchers using different techniques of content analysis, different CSR indicators and different sources of information resulted in the absence of a unified methodology of corporate social information disclosure and its research the obtained study results are hardly comparable and in some cases even contradictory.